Chronic pain and migration-related factors among Syrian refugees: a cross-sectional study. (13th November 2019) - Strømme, E M; Haj-Younes, J; Hasha, W; Fadnes, L T; Kumar, B; Diaz, E
Abstract: Background: Refugees display high rates of chronic pain. However, the relationship between refugee-related exposures introduced along their migration trajectories and the development of chronic pain remains unclear. The aim of this study was to assess the impact of stressors induced at various migration stages on chronic pain in Syrian refugees. Methods: This is a cross-sectional survey among adult Syrian refugees in Lebanon and in Norway. We conducted logistic regression to study the associations between chronic pain and migration-related factors experienced prior to or during flight (trauma exposure, migrating alone and detainment) and after arrival in a new country (legal status, social relationships, living conditions and access to health care). Results: Altogether 827 Syrians participated (response rate 85%). The mean age was 33 years and 41% were women. The overall prevalence of chronic pain was 30%. The mean WHO Quality of Life (WHOQOL) domain scores for both social relationships (13.4) and environment (10.2) were significantly lower among those reporting chronic pain, with low scores indicating less satisfaction. Regression analyses revealed an association between chronic pain and exposure to trauma (adjusted odds ratio (AOR) 2.5 (1.8; 3.4)), but no clear association between chronic pain and migrating alone or history of detention. Poor social relationships (AOR 1.9 (1.2; 3.1)), poor support from friends (AOR 1.5 (1.0; 2.1)) and poor living place (AOR 1.4 (1.0; 2.0)) were associated with reporting chronic pain, although associations reduced when adjusting for traumatic experiences. The associations between chronic pain and poor economy (AOR 1.6 (1.1; 2.5)) and poor access to health care (AOR 1.5 (1.0; 2.1)) persisted after trauma exposure adjustment. Conclusions: We found a strong relationship between trauma exposure and chronic pain. Further, perceived poor economy and poor access to health care were associated with chronic pain regardless of trauma history. Key messages: Trauma exposure, perceived poor economy and poor access to health care are associated with chronic pain among Syrian refugees. Public health care interventions should consider the combined impact of risk factors throughout the migration trajectory.